Sleep problems from age two to five years and neurological outcome in children born extremely preterm: a cross-sectional study - Stangenes, Kristine Marie; Hysing, Mari; Vollsæter, Maria; Elgen, Irene Bircow; Markestad, Trond; Bjorvatn, Bjørn (Frontiers in Pediatrics, 2025)
IntroductionPremature birth is associated with a higher risk of sleep problems and neurodevelopmental disabilities (NDD). We examined relationships between sleep problems and cognitive, motor, and sensory functions in a national cohort of five-year-old children born extremely preterm (EPT) with the purpose of identifying possible means of improving developmental outcomes.MethodsThis study was part of a national cohort study of all children born extremely preterm, defined here as gestational age less than 28 completed weeks, or birth weight below 1,000 g, born in Norway in 1999 and 2000. Parents completed a structured retrospective questionnaire at age five to assess sleep problems from ages two to five years. We assessed cognitive function using the Wechsler Preschool and Primary Scale of Intelligence-Revised (WPPSI-R), evaluated motor function with the Movement Assessment Battery for Children (M-ABC) and classified cerebral palsy (CP) according to the Gross Motor Function Classification System (GMFCS). NDD was graded from no NDD (no disabilities) to NDD 2 and 3 (moderate and severe disability).ResultsOf 372 eligible children, 253 (68%) participated. Parents reported that 28.5% had general sleep problems from ages two to five years. Prevalences of specific problems were 21.7% for nighttime awakenings, 17.8% for difficulty falling asleep, 5.9% for early morning awakening and 1.6% for late morning awakening. Children with Full scale IQ < 85 were at increased risk of general sleep problems (adjusted odds ratio - aOR 1.8), as well as nighttime awakenings (aOR 2.8), and early morning awakenings (OR 2.9), but not for difficulty falling asleep compared to those with higher IQ levels.EPT children with moderate to severe NDD (NDD 2 and 3) showed a higher prevalence of general sleep problems [adjusted odds ratio (aOR) 3.9], nighttime awakenings (aOR 4.8), and early morning awakenings (OR 7.9) compared to those with no NDD (NDD 0).ConclusionGeneral and specific sleep problems were associated with low cognitive function and moderate to severe NDD. Our findings underscore the importance of addressing sleep within a comprehensive care framework for EPT children and highlight the need for addressing and target interventions for sleep problems.